Evaluation performance in health regions in Brazil - Liza Yurie Teruya Uchimura; Eronildo Felisberto; Edgar Rodrigues Fusaro; Maria Paula Ferreira; Ana Luiza d' Ávila Viana
Abstract Objectives: To propose a regional synthetic indicator (ISR) to evaluate the health system performance in Brazilian regions based on a national database source available free of charge in a global network of computers. Methods: a cross-sectional study using secondary data, considered seven variables of five dimensions in the health system (population's health conditions, health system coverage, financing, human resources and SUS production) analyzed from a survey of 438 Brazilian regions and adopted factor analysis and cluster models, conditioned by variables, such as: socioeconomic development, offering and service complexity and which resulted in a grouping of five strata. Results: mapping and scheduling based on ISR in health regions in Brazil and a detailed analysis of different indicators that compose them. The regions that showed better perfor-mance are in the Southeast, South and Midwest. Conclusions: This article sums efforts of other authors to extend the evaluation studies in health systems in a regional level. In addition, it is expected that the researches broaden their scope and implement the discussions about the process of regionalization in order to provide health policies, a universalized access and care comprehensiveness.